Mark's Sale & Feed Livery Stable (Mille Lacs County Historical Society, 101 South 10th Ave., Princeton, MN 55371 http://www.rootsweb.ancestry.com/~mnmlchs)
ae453036681ff1b9ab97b1adeb71cee0
United States
Minnesota
Mille Lacs
Princeton
ae453036681ff1b9ab97b1adeb71cee0
Keywords: Livery Stable; Agriculture